(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The ecology of tuberculosis disease consists of a complex phe¬nomena. This reveals a multitude of interaction of physical and cultural environ¬ment in relation to the infection, morbidity and mortality of tuberculosis disease. Thus in this paper, emphasis is given to outline some of the ecological factors and to demonstrate the ways in which such ecological factors as - terrain, tubercle bacillus, factors affecting host-resistance, over-crowded dwellings, social factors, space, ventilation, spirituous liquor etc. are intimately linked with the disease. The spatial organization of these ecological factors in the world is more heterogeneous in character. Each of these factors is linked with one another in complex relationship. In short, the paper concentrates on three major techni¬ques, of describing and measuring the causes of prevalence of infection, morbidity and mortality of tuberculosis disease in different parts of the world, which are given as under: